The Potential Of Oee Measure For Sustainable Environment In Palm Oil Mill: A Review - Wan Mahmood, Wan Hasrulnizzam; Abdullah, Ilyana; MD FAUADI , MUHAMMAD HAFIDZ FAZLI; Ab Rahman, Mohd Nizam (Sci.Int.(Lahore), 2014)
The purposes of this paper are to review and explore the potential of overall equipment effectiveness (also known as OEE) measures on environmental sustainability in palm oil mill operation. Literature review on OEE and current sustainable palm oil mill research, and semi-structured interview on relevant persons on the business nature have been conducted to achieve the determined objectives. The result is presented in a conceptual model to show the potential relationship between the three stated keywords. The model shows that OEE measure initially has positive influenced on environmental sustainability development in palm oil mill especially for reduction of greenhouse gasses emissions, utilisation of raw material, pollution control of soil, air, and water, and utilisation of natural resources. The findings also can be used to understand the effect of OEE measures on the realization of sustainable environment in the palm oil mill.